2001
DOI: 10.1111/j.1572-0241.2001.04126.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological variability of fecal calprotectin in patients referred for colonoscopy without colonic inflammation or neoplasm1

Abstract: Day-to-day variation of fecal calprotectin is considerable in patients without colonic inflammation or neoplasm, for whom the pattern of stabile low fecal calprotectin may seem to be a valid negative predictor. The origin and pattern of fecal calprotectin excretion deserve further attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 9 publications
3
18
0
Order By: Relevance
“…Thus, children exhibiting poor growth may have higher intestinal permeability, leading to a higher FC concentration. In this study, the wide range of inter- and intra-individual variation in calprotectin excretion in feces may also be explained by normal biological variability, with day-to-day variations as have been described previously in adults and children [ 30 , 47 , 48 ].…”
Section: Discussionsupporting
confidence: 56%
“…Thus, children exhibiting poor growth may have higher intestinal permeability, leading to a higher FC concentration. In this study, the wide range of inter- and intra-individual variation in calprotectin excretion in feces may also be explained by normal biological variability, with day-to-day variations as have been described previously in adults and children [ 30 , 47 , 48 ].…”
Section: Discussionsupporting
confidence: 56%
“…Day-to-day variation of FC was demonstrated by Husebay et al[ 13 ] in patients without colonic inflammation or neoplasm and confirmed by Moum et al[ 14 ], in patients with mild-to-moderate active CD, where significant differences in 63 pairs of stool samples collected in 2 consecutive days were found. A lower variability was observed in fecal samples collected for 3 d from 93 CD patients in clinical remission[ 15 ].…”
Section: Pitfalls In Fc Assessmentmentioning
confidence: 65%
“…From approximately that age up to 17-year-old healthy children, calprotectin concentrations seem to be similar to that of healthy adults [15,16]. In adults, a day-to-day variation in calprotectin excretion in serial samples has been demonstrated both in IBD patients and in controls [17,18]. However, a recent study in a large cohort of clinically quiescent CD patients showed a low day-to-day variation in calprotectin concentrations obtained on 3 consecutive days [19].…”
Section: Calprotectinmentioning
confidence: 99%